An assessment of the financial sustainability and performance of Philippine water districts - Velasco, Lawrence G. (2021)
This study evaluates the consolidated financial condition and performance of local water districts (LWDs) in the Philippines. Water districts are government-owned or controlled corporations (GOCCs) tasked to construct, operate, maintain, and expand water and sanitation systems in the countryside. They are instrumental in the Philippines' objective to attain 100-percent water supply and sanitation access by 2036. National data show that the consolidated financial performance of LWDs has improved from 2009 to 2028, as reflected in their high and stable cash flows, high debt service coverage ratios, and lower debt ratios. With the aggressive spending program of the government on water infrastructure, lower debt ratios are needed to prepare LWDs to achieve the 2023 and the 2030 goals of universal access to water supply and sanitation. However, the government's spending plans are so ambitious that the current balance sheets of LWDs cannot sustain the planned investments financed through debt. The national government needs to bolster the balance sheets of LWds by infusing fresh equity of PHP 22 billion to PHP 56 billion to achieve the Philippines' 2030 water supply and sanitation targets. The study likewise shows a significant disparity in water investments across the country's different regions, which impacts the uneven water service coverage throughout the Philippines.
Keywords: Water districts; Financial performance; Water supply